Colonial representations of Macao and the Macanese: Circulation, knowledge, identities and challenges for the future - Matos, Patrícia Ferraz de (2021)
This article intends to contribute towards the study of harbour cities, reflecting on the circulation of things and people, matters associated with national borders and multiple identities that cross paths there. Considering the history of Macao, its relationship with the Portuguese colonial empire and the challenges posed to the Macanese identity, this article intends to analyse representations of Macao and the Macanese produced in Portugal during the colonial period, considering some of them may still have repercussions today. Representations in generally accessed documents, such as the periodical press, will be analysed, as will events, such as great exhibitions, that were directed to a broader audience and which were frequently incorporated into colonial propaganda. By realizing that even today the movement towards the internationalization of Macao and China itself also involves Portugal, one concludes this is an interesting place for reflecting on power strategies, the circulation of individuals and the formation of identities.